Neonate personality affects early-life resource acquisition in a large social mammal. (9th August 2022) - Amin, Bawan; Jennings, Dómhnall J; Norman, Alison; Ryan, Andrew; Ioannidis, Vasiliki; Magee, Alice; Haughey, Hayley-Anne; Haigh, Amy; Ciuti, Simone
Abstract: Although it is widely acknowledged that animal personality plays a key role in ecology, current debate focuses on the exact role of personality in mediating life-history trade-offs. Crucial for our understanding is the relationship between personality and resource acquisition, which is poorly understood, especially during early stages of development. Here we studied how among-individual differences in behavior develop over the first 6 months of life, and their potential association with resource acquisition in a free-ranging population of fallow deer ( Dama dama ). We related neonate physiological (heart rate) and behavioral (latency to leave at release) anti-predator responses to human handling to the proportion of time fawns spent scanning during their first summer and autumn of life. We then investigated whether there was a trade-off between scanning time and foraging time in these juveniles, and how it developed over their first 6 months of life. We found that neonates with longer latencies at capture (i.e., risk-takers) spent less time scanning their environment, but that this relationship was only present when fawns were 3–6 months old during autumn, and not when fawns were only 1–2 months old during summer. We also found that time spent scanning was negatively related to time spent foraging and that this relationship became stronger over time, as fawns gradually switch from a nutrition rich (milk) to a nutrition poor (grass) diet. Our results highlight a potential mechanistic pathway in which neonate personality may drive differences in early-life resource acquisition of a large social mammal. Abstract : There is an ever-increasing interest in behavioral differences between individuals, or "animal personality". Here we show how these differences develop over the first six months in fawns of a fallow deer population. Individuals that behave boldly as newborns when captured by humans still display bold behavior months later, which may allow them to acquire more resources. These findings shed light on the role that personality plays in ecology and evolution early in life.